SPATIAL CONTINUITY OF DENDROMETRICS CHARACTERISTICS OF PINUS (Pinus pinaster Aiton) AND SOIL ATTRIBUTES - SIQUEIRA, GLÉCIO M.; DAFONTE, JORGE; VÁZQUEZ, EVA VIDAL; GONZÁLEZ, ANTONIO PAZ; MONTANARI, RAFAEL (Revista Brasileira de Engenharia de Biossistemas, 2009)
The objective of this study was to evaluate the relationship and spatial pattern of dendrometricscharacteristics of pine (Pinus pinasterAiton) and soil properties. The measurements were made at0.25 ha area planted with Pinus pinaster in Muras (Province of Lugo, Galicia, Spain). The soil propertiessampled were: the tree diameter at base (DB), the diameter at 0.30 m height (D30), the diameter atbreast height (1.3 m height, DAP), height trees (ALT), depth of the soil profile (PROF) and the soilapparent electric conductivity to 0.3 m depth (CEa-H) and 1.5 m depth (CEa-V). The semivariogramallowed to detect the spatial dependence in all studied propertied, except for the depth of the soilprofile that showed pure nugget effect. Data showed moderate spatial dependence ratio betweensamples. It was not found a similar spatial pattern between the soil and plant studied propertiesmaps.